Acute intestinal obstruction in adults: etiology, clinical presentation, investigations and management: a longitudinal study - Bargaje, Pankaj; Wasnik, Nitin (International Surgery Journal, 2020)
Background: Aim of the study was to evaluate the causes of acute intestinal obstruction, modes of presentation and outcome of conservative and operative management in acute intestinal obstruction. Methods: The study was conducted in tertiary care academic hospital from November 2017 to October 2019. 60 Patients over 18 years of age who were diagnosed with acute intestinal obstruction were included in this study. Results: The result of present study showed that mean age distribution was 46±15.4 years. Incidence in males was more compared to females. Pain in abdomen was found in 54 (90%), vomiting in 38 (63%), distension of abdomen in 37 (61%) and constipation in 42 (70%) as patient’s chief complaint. Commonest cause was adhesions followed by obstructed inguinal hernia. Conclusions: From the result of present longitudinal study it can be concluded that conservative management can be tried in patients with previous history of abdominal operation and intestinal tuberculosis. Acute intestinal obstruction was more common in male than female. X ray abdomen in standing position and USG helps in ascertaining the site of intestinal obstruction.